Ghana : 2017 Article IV Consultation, Fourth Review Under the Extended Credit Facility Arrangement, Request for Waiver for Nonobservance of Performance Criteria, and Request for Extension and Rephasing of the Arrangement-Press Release; Staff Report; Staff Supplement; and Statement by the Executive Director for Ghana. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that Ghana has shown mixed macroeconomic performance in recent years, with significant shocks being amplified by policy slippages and resulting external and domestic imbalances. Growth in 2016 was 3.5 percent, the lowest level in two decades. A recovery of growth is expected in 2017-18, owing to an increase in oil production, declining inflation, and lower imbalances with the right policy implementation. Inflation has continued to decline and the exchange rate has been broadly stable. The external position has continued to improve, supported by strong foreign investors' participation in the domestic debt market. Over the medium term, both the fiscal deficit and the current account deficit are projected to decline gradually.